IMPLEMENTASI METODE RATIONAL UNIFIED PROCESS(RUP) UNTUK RANCANG BANGUN SISTEM INFORMASI PENGAJUAN CUTI DI PT. BETTS INDONESIA BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL - Fariz, Muchammad; Noval Riswandha, Muhammad (LPPM ITB Yadika Pasuruan, 2024)
Abstract: Almost all companies still use the manual method in terms of applying for leave. See the progress of increasingly sophisticated technology. Requires a computerized leave application information system. The benefits include facilitating the recording process, both submitting leave for each employee and managing leave confirmation for each employee. Development is carried out using the RUP (Rational Unified Process) method and design designs using the Unified Modeling Language (UML) visual modeling. Using the Laravel framework. The hope of the information system created is that it can help submit employee leave efficiently, so that it can help and facilitate leave requests